Negotiating between belief and custom: the encounters of Han Muslim converts in China - Ma, Qiang (Critical Asian studies, 2024)
The conversion of Han Chinese in the Peoples Republic of China (PRC) to Islam is a complex and dynamic process that goes beyond the mere adoption of a new faith. Potential converts undergo a multifaceted journey involving learning about Islam, reflecting on Hui and Han ethnic cultures and customs, and understanding the historical relationship between Islam as a religion and ethnic Hui Chinese people. Through this process, Han converts gradually develop a pluralistic and multilayered identity that encompasses their Han ethnicity and Muslim faith. The article emphasizes the importance of daily inter-group interactions and the use of various strategies to resolve conflicts while adhering to Islamic beliefs. It introduces a theoretical framework consisting of discursive, local, and configurable values to analyze the nuances of everyday experiences among Han converts. This framework provides a structured approach to understanding the complexities of identity formation and enrich ongoing discussions within the Islamic anthropological research community.(Crit Asian Stud/GIGA)